2017
DOI: 10.1097/md.0000000000006791
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between SRD5A2 rs9282858 polymorphism and the susceptibility of prostate cancer

Abstract: The pathogenetic mechanism of prostate cancer (PCa) has not been understood completely, and gene polymorphisms have been demonstrated to play a critical role in the course. It has been reported that rs9282858 polymorphism of steroid 5-α-reductase type 2 (SRD5A2) may affect the susceptibility of PCa, but some researches showed different results. We therefore carried out a meta-analysis to clarify this relationship.Relevant studies were identified through PubMed and Chinese National Knowledge Infrastructure data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…After reading the full texts, 7 articles were excluded to duplicates (n = 5), review (n = 1), or lack of the relevant date (n = 1). Finally, a total of 33 case-control studies from 27 publications [ 14 , 22 , 23 , 30 – 53 ] which met our inclusion criteria, including 7276 cases and 9667controls. The main characteristics of each study identified are listed in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After reading the full texts, 7 articles were excluded to duplicates (n = 5), review (n = 1), or lack of the relevant date (n = 1). Finally, a total of 33 case-control studies from 27 publications [ 14 , 22 , 23 , 30 – 53 ] which met our inclusion criteria, including 7276 cases and 9667controls. The main characteristics of each study identified are listed in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, 12 case-control studies were performed in Asians, [ 22 , 23 , 36 38 , 40 , 41 , 44 , 45 , 50 , 52 , 53 ] 12 in Caucasians, [ 14 , 31 – 36 , 39 , 42 , 46 , 47 , 51 ] 5 in Mixed. [ 30 , 36 , 43 , 48 , 49 ] As for study design, there were 2 FB, [ 30 , 31 ] 14 PB, [ 14 , 23 , 32 , 33 , 36 , 37 , 39 , 41 – 45 , 48 , 50 , 53 ] and 11 HB. [ 22 , 34 , 35 , 38 , 40 , 43 , 46 , 47 , 49 , 51 , 52 ] Eleven studies described the specific location of CRC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another amino acid substitution at the same position (p.Ala49Thr) was present in a hemizygous state in the father and in a heterozygous state in the healthy sibling with apparently no effect on normal sexual development. This variant was previously described in association with hypospadias [19][20][21] and prostate cancer, although with inconsistent findings [22,23].…”
Section: A B Discussionmentioning
confidence: 82%
“…20 Relevant researches indicate that one in three men aged over 80 years needs treatment to relieve BPH-induced symptoms. 18,19,21,22 Apart from age, multiple factors play certain roles in the occurrence and development of BPH including sex steroid hormone levels and genetic predisposition, [23][24][25][26][27] obesity, free prostate specific antigen (PSA) level, cardiovascular disease (CVD), the use of -blocker medications, 28,29 type 2 diabetes mellitus (DM), 30 and hypertension. 31 Moreover, BPH is also considered as a component of the metabolic syndrome (Mets).…”
Section: Introductionmentioning
confidence: 99%